Efficiency and mechanism of the degradation of ciprofloxacin by the oxidation of peroxymonosulfate under the catalysis of a Fe3O4/N co-doped sludge biochar. (June 2023) - Zheng, Dayang; Zou, Jiali; Xu, Hao; Wu, Min; Wang, Yayi; Feng, Cang; Zheng, Eryang; Wang, Teng; Shi, Yuxiang; Chen, Yongjian; Li, Binyang
Abstract: A novel and recyclable composite material, Fe3 O4 /N co-doped sludge biochar (FNBC), was developed from original sludge biochar (BC) and found to have excellent stability and superior catalytic capacity during the ciprofloxacin (CIP) degradation under the action of peroxymonosulfate (PMS). In the FNBC/PMS system, an approximately complete removal of CIP was achieved within 60 min under the condition of 1.0 g/L FNBC, 3.0 mM PMS, and 20 mg/L CIP, which was about 2.08 times of that in BC/PMS system (48.01%). Besides, FNBC/PMS system could effectively remove CIP under the influence of wide pH (2.0–10.0) or inorganic ions compared with BC/PMS system. Moreover, it was found that there were radical produced under the effect of Fe element, defects, functional groups, pyridinic N and pyrrolic N and non-radical caused by graphitic N, carbon atoms next to the iron atoms and better adsorption capacity in the FNBC/PMS system. It was observed that the contribution of hydroxyl radical (OH), sulfate radical (SO4 − ) and singlet oxygen ( 1 O2 ), which were the main reactive oxygen species, during the CIP degradation, were 75.80%, 11.49% and 10.26%, respectively. Furthermore, total organic carbon (TOC) variation was analyzed and the degradation pathway of CIP was speculated. The application of this material could combine the recycling of sludge with the effective degradation of refractory organic pollutant, providing an environmentally friendly and economic method. Graphical abstract: Image 1 Highlights: Fe3 O4 /N co-doped sludge biochar (FNBC) showed 2.08-fold higher activity to biochar. FNBC/PMS system has radical and non-radical pathways to oxidize CIP. OH played a primary role in the CIP degradation in FNBC/PMS system. The degradation pathway of CIP was speculated. FNBC had excellent stability and recyclability.